The handbook of gender, communication, and women's human rights - Gallagher, Margaret; Montiel, Aimee Vega
A timely feminist intervention on gender, communication, and women's human rights The Handbook on Gender, Communication, and Women's Human Rights engages contemporary debates on women's rights, democracy, and neoliberalism through the lens of feminist communication scholarship. The first major collection of its kind published in the COVID-19 era, this unique volume frames a wide range of issues relevant to the gender and communication agenda within a human rights framework. An international panel of feminist academics and activists examines how media, information, and communication systems contribute to enabling, ignoring, questioning, or denying women's human and communication rights. Divided into four parts, the Handbook covers governance and policy, systems and institutions, advocacy and activism, and content, rights, and freedoms. Throughout the text, the contributors demonstrate the need for strong feminist critiques of exclusionary power structures, highlight new opportunities and challenges in promoting change, illustrate both the risks and rewards associated with digital communication, and much more. Offers a state-of-the-art exploration of the intersection between gender, communication, and women's rights Addresses both core and emerging topics in feminist media scholarship and research Discusses the vital role of communication systems and processes in women's struggles to claim and exercise their rights Analyzes how the COVID-19 pandemic has exacerbated structures of inequality and intensified the spread of disinformation Explores feminist-based concepts and approaches that could enrich communication policy at all levels Part of the Global Handbooks in Media and Communication Research series, TheHandbook of Gender, Communication, and Women's Human Rights is essential reading for advanced undergraduate and graduate students in media studies, communication studies, cultural studies, journalism, feminist studies, gender studies, global studies, and human rights programs at institutions around the world. It is also an invaluable resource for academics, researchers, policymakers, and civil society and human rights activists.